Studies on Wrightoporia (Basidiomycota) from southern Brazil - Westphalen, Mauro Carpes; Reck, Mateus A.; Da Silveira, Rosa Mara Borges (Phytotaxa, 2014)
In recent surveys of polyporoid fungi from Rio Grande do Sul State, southern Brazil, some interesting resupinate specimens belonging to the genus Wrightoporia were found. Wrightoporia araucariae is described as new, based on the fragile, whitish basidiomes which grow exclusively on Araucaria angustifolia; and W. bracei is recorded for the first time from Rio Grande do Sul State. In addition, W. efibulata is synonymized to Wrightoporia bracei based on collected specimens and herbarium material. The species are described, illustrated and discussed, and an identification key to the neotropical species of Wrightoporia is provided.